Analysis of the Influence of Performance Assessment, Mutation Patterns and Talent Management on Employee Performance with Organizational Culture as a Moderating Variable : Study on Employees of the East Java III Regional Tax Office - Afia Maria Ulfah; Muryati Muryati; Adya Hermawati (Brilliant International Journal Of Management And Tourism, 2025)
The purpose of this study is to analyze the influence of performance appraisal, mutation patterns and talent management on the performance of Directorate General of Taxes (DGT) Employees with organizational culture as a moderating variable The type of research used in this study is quantitative research. The population in this study were all employees of the East Java III Regional Office of the Directorate General of Taxes, with a total of 1,522 employees. The method of determining the number of samples using the Slovin formula, which is 132.60 and rounded up to 132. Based on data and information, the researcher also took samples using the proportionate stratified random sampling technique. The researcher used the Partial Least Square (PLS) data analysis technique, and the software chosen by the researcher was SmartPLS version 4. The results of this study indicate that improvements in performance appraisal systems can lead to better employee performance. However, despite becoming more structured, mutation patterns do not appear to significantly impact performance outcomes. Similarly, even with strengthened talent management practices, there is no clear improvement in employee performance. A strong organizational culture does contribute to enhanced employee performance. Nonetheless, it does not serve as a moderating factor in the relationship between performance appraisal, mutation patterns, or talent management and employee performance.